Weathering the storm: A qualitative study of social prescribing in urban and rural Scotland during the COVID-19 pandemic. (June 2021) - Fixsen, Alison; Barrett, Simon; Shimonovich, Michal
Objectives: The non-clinical approach known as social prescribing aims to tackle multi-morbidity, reduce general practitioner (GP) workload and promote wellbeing by directing patients to community services. Usual in-person modes of delivery of social prescribing have been virtually impossible under social distancing rules. This study qualitatively examined and compared the responses of three social prescribing schemes in Scotland to the COVID-19 pandemic. Methods: We interviewed a theoretical sample of 23 stakeholders in urban and rural social prescribing schemes at the start of COVID-19 pandemic. Follow-up interviews with a representative sample were conducted around 10 months later. Interviewees included social prescribing coordinators (SPCs) GPs, managers, researchers and representatives of third sector organizations. Interview transcripts were analysed in stages and an inductive approach to coding was supported by NVivo. Results: Findings revealed a complex social prescribing landscape in Scotland with schemes funded, structured and delivering services in diverse ways. Across all schemes, working effectively during the pandemic and shifting to online delivery had been challenging and demanding; however, their priorities in response to the pandemic had differed. With GP time and services stretched to limits, GP practice-attached 'Link Workers' had taken on counselling and advocacy roles, sometimes for serious mental health cases. Community-based SPCs had mostly assumed a health education role, and those on the Western Isles of Scotland a digital support role. In both rural or urban areas, combatting loneliness and isolation – especially given social distancing – remained a pivotal aspect of the SPC role. Conclusion: This study highlights significant challenges and shifts in focus in social prescribing in response to the pandemic. The use of multiple digital technologies has assumed a central role in social prescribing, and this situation seems likely to remain. With statutory and non-statutory services stretched to their limits, there is a danger of SPCs assuming new tasks without adequate training or support.